2021
DOI: 10.1002/ece3.7925
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐based adaptability of Phragmites australis to the effects of soil water and salinity in the Yellow River Delta

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Generally, determination of the CSR strategy is considered useful for comparison of different plant species 55 ; however, it can also be used for monitoring the response to environmental stressors, including salinity 56 . In the case of R. acris , intensifying salinity (60 and 90 mmol dm −3 NaCl) caused a slight but significant shift from a competition-oriented to a disturbance-oriented strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, determination of the CSR strategy is considered useful for comparison of different plant species 55 ; however, it can also be used for monitoring the response to environmental stressors, including salinity 56 . In the case of R. acris , intensifying salinity (60 and 90 mmol dm −3 NaCl) caused a slight but significant shift from a competition-oriented to a disturbance-oriented strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This helped plants distribute the available resources more effectively among various traits. This helped achieve trade-offs appropriately between vegetative and reproductive growth (Zhou et al 2021). The growth can help occupy the dominant niche via rapid reproduction, growth and relatively huge plant organs (in other words, high LA and high SLA).…”
Section: Differences In Cwms For Csr Ecological Strategies In Various...mentioning
confidence: 99%
“…Adaptations to salinity were studied in natural conditions of river delta wetland ecosystems, and it was found that increasing salinity was more important for morpholog-ical and physiological variability in comparison to the effects of soil water content [220]. In particular, plant height, leaf area, and stem diameter decreased but leaf water content increased with increasing salinity.…”
Section: Phargmites Australismentioning
confidence: 99%